Morphological ontogeny of Zachvatkinibates latilamellatus (Acari: Oribatida: Punctoribatidae), and comments on Zachvatkinibates Shaldybina - Seniczak, Stanisław; Seniczak, Anna; Kaczmarek, Sławomir; Marquardt, Tomasz; Sarsenova, Bibigul (Zootaxa, 2020)
The morphological ontogeny of Zachvatkinibates latilamellatus Bayartogtokh & Aoki, 1998 is described and illustrated. The juveniles of this species are light brown, with several pairs of small, sclerotized depressions on the gastronotum, which are unique in Zachvatkinibates Shaldybina, 1973. The larva has 12 pairs of gastronotal setae, including h3, all are inserted on unsclerotized integument; nymphs have 15 pairs, of which c-series is inserted on individual sclerites, d-, l-, h-series and p1 are on sclerotized integument, and p2 and p3 on unsclerotized integument. In all juveniles, a porose humeral organ is present.